Imaging analysis of human metapneumovirus-infected cells provides evidence for the involvement of F-actin and the raft-lipid microdomains in virus morphogenesis - Jumat, Muhammad Raihan (2015)
Backgound: Due to difficulties of culturing Human metapneumovirus (HMPV) much of the current understanding of HMPV replication can be inferred from other closely related viruses. The slow rates of virus replication prevent many biochemical analyses of HMPV particles. In this study imaging was used to examine the process of HMPV morphogenesis in individually infected LLC-MK2 cells, and to better characterise the sites of HMPV assembly. This strategy has circumvented the problems associated with slow replication rates and allowed us to characterise both the HMPV particles and the sites of HMPV morphogenesis. Methods: HMPV-infected LLC-MK2 cells were stained with antibodies that recognised the HMPV fusion protein (F protein), attachment protein (G protein) and matrix protein (M protein), and fluorescent probes that detect GM1 within lipid-raft membranes (CTX-B-AF488) and F-actin (Phalloidin-FITC). The stained cells were examined by confocal microscopy, which allowed imaging of F-actin, GM1 and virus particles in HMPV-infected cells. Cells co-expressing recombinant HMPV G and F proteins formed virus-like particles and were co-stained with antibodies that recognise the recombinant G and F proteins and phalloidin-FITC and CTX-B-AF594, and the distribution of the G and F proteins, GM1 and F-actin determined. Results: HMPV-infected cells stained with anti-F, anti-G or anti-M revealed a filamentous staining pattern, indicating that the HMPV particles have a filamentous morphology. Staining of HMPV-infected cells with anti-G and either phalloidin-FITC or CTX-B-AF488 exhibited extensive co-localisation of these cellular probes within the HMPV filaments. This suggested that lipid-raft membrane domains and F-actin structures are present at the site of the virus morphogenesis, and are subsequently incorporated into the HMPV filaments. Furthermore, the filamentous virus-like particles that form in cells expressing the G protein formed in cellular structures containing GM1 and F-actin, suggesting the G protein contains intrinsic targeting signals to the sites of virus assembly. Conclusions: These data suggest that HMPV matures as filamentous particles and that virus morphogenesis occurs within lipid-raft microdomains containing localized concentrations of F-actin. The similarity between HMPV morphogenesis and the closely related human respiratory syncytial virus suggests that involvement of F-actin and lipid-raft microdomains in virus morphogenesis may be a common feature of the Pneumovirinae.